1999
DOI: 10.2307/3237060
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and process in above‐ground and below‐ground components of grassland ecosystems

Abstract: Abstract. This paper describes patterns of below‐ground components in grassland ecosystems. It provides estimates of the contribution of below‐ground organs to the total phytomass of the community and of different species to the below‐ground phytomass; it describes the distribution of above‐ and below‐ ground organs of different species and the spatial and temporal correlation between above‐ground and below‐ground phyto‐mass – both total standing crop and net primary production. 10 Siberian grasslands (meadow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 16 publications
(13 reference statements)
7
67
0
4
Order By: Relevance
“…The fastest growth of below-ground organs can occur in different parts of growing season reflecting the annual cycle of vegetative activity (Titlyanova et al 1999). In the present study, mostly significantly higher values of RNPP were assessed in the first half of the 1992 growing season through all treatments.…”
Section: Results and Duscussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The fastest growth of below-ground organs can occur in different parts of growing season reflecting the annual cycle of vegetative activity (Titlyanova et al 1999). In the present study, mostly significantly higher values of RNPP were assessed in the first half of the 1992 growing season through all treatments.…”
Section: Results and Duscussionmentioning
confidence: 45%
“…Only a few studies related below-ground primary production (BNPP) with climate variables and, in addition, contradictory data on root growth and below-ground biomass were published (e.g. Ibrahim et al 1997, Titlyanova et al 1999, Gill et al 2002, Hejduk and Hrabě 2003.…”
mentioning
confidence: 99%
“…3), one might argue that aboveground biomass is a poor proxy for soil OC input. However, under the assumption that root residue inputs are correlated with the aboveground biomass (evidence is given by Titlyanova et al, 1999, who observed significant correlations (p < 0.01, R > 0.5) between the aboveground and belowground biomass of typical plants in Siberian grasslands), one can conclude that both aboveground and belowground soil OC inputs were comparable between all three soil types. Wong et al (2010) argued that small OC stocks in saltaffected soils can also be the result of erosion-induced OC losses, as sodic soils are particularly prone to erosion.…”
Section: Soil Oc Stocks Along the Salinity Gradientmentioning
confidence: 92%
“…On the other hand, results of other authors indicate that root biomass and root length were lower in the drought year than in the wet year (e.g. Hayes, Seastedt, 1987;Andrzejewska, 1991;Titlyanova et al, 1999). Also Hui and Jackson (2006) found strong negative relationships of root fraction with mean annual temperature (MAT) and MAP across sites, however, temporal relationships of root fraction and climatic variables within sites were more complicated and site-specific.…”
Section: Introductionmentioning
confidence: 94%